2008
DOI: 10.1113/jphysiol.2008.159905
|View full text |Cite
|
Sign up to set email alerts
|

A common polymorphism in the brain‐derived neurotrophic factor gene (BDNF) modulates human cortical plasticity and the response to rTMS

Abstract: The brain-derived neurotrophic factor gene (BDNF) is one of many genes thought to influence synaptic plasticity in the adult brain and shows a common single nucleotide polymorphism (BDNF Val66Met) in the normal population that is associated with differences in hippocampal volume and episodic memory. It is also thought to influence possible synaptic changes in motor cortex following a simple motor learning task. Here we extend these studies by using new non-invasive transcranial magnetic stimulation (TMS) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
475
10
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 615 publications
(537 citation statements)
references
References 28 publications
25
475
10
12
Order By: Relevance
“…Similarly, no relationship was seen between synaptic plasticity (as assessed by PAS) and serum BDNF levels in the whole study sample. In terms of BDNF genotype, we did not confirm a prior report that Val/Val homozygotes demonstrated greater MEP amplitude after PAS (Cheeran et al, 2008).…”
Section: Discussioncontrasting
confidence: 54%
“…Similarly, no relationship was seen between synaptic plasticity (as assessed by PAS) and serum BDNF levels in the whole study sample. In terms of BDNF genotype, we did not confirm a prior report that Val/Val homozygotes demonstrated greater MEP amplitude after PAS (Cheeran et al, 2008).…”
Section: Discussioncontrasting
confidence: 54%
“…Kleim et al [2006] used a motor training task involving the fingers to show that individuals with val66met had significantly lower training dependent increases in the amplitude of motor evoked potentials and reduced motor map reorganization in cerebral cortex. A recent study also showed that individuals with the met allele had impaired responses to median nerve paired associative stimulation and a probe of cortical plasticity using tDCS and TMS [Cheeran et al, 2008]. This information strengthens the link between the basic science model of neuronal plasticity presented above and clinical plasticity, but there is limited information about this mutation in children or adults with brain injuries.…”
Section: Genetic Influences On Brain Plasticitymentioning
confidence: 95%
“…Conversely, the reduction in presynaptic activity induced by the cathodal tDCS (combined with the postsynaptic hyperpolarization) could weaken the synaptic connections (Bindman et al, 1964a;Bindman et al, 1964b;Cheeran et al, 2008).…”
Section: Tdcs-induced Changes In Cortical Excitabilitymentioning
confidence: 99%